2015
DOI: 10.1186/s40659-015-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

In ovo administration of human recombinant leptin shows dose dependent angiogenic effect on chicken chorioallantoic membrane

Abstract: BackgroundLeptin, the cytokine produced by white adipose tissue is known to regulate food energy homeostasis through its hypothalamic receptor. In vitro studies have demonstrated that leptin plays a major role in angiogenesis through binding to the receptor Ob-R present on ECs by stimulating and initiating new capillary like structures from ECs. Various in vivo studies indicate that leptin has diverse effect on angiogenesis. A few reports have showed that leptin exerts pro angiogenic effects while some suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
3
22
0
1
Order By: Relevance
“…Although the sequence of chicken leptin gene was a matter of intense debate for almost 20 years (Taouis et al, 1998 ; Ashwell et al, 1999 ; Seroussi et al, 2016 ), the chicken leptin receptor sequence however was found to have at least 60% homology with the mammalian orthologs with highly conserved motifs in the transmembrane domain (Horev et al, 2000 ; Ohkubo et al, 2000 ). Moreover, previous in vitro and in vivo studies have shown that chicken leptin receptor is responsive to recombinant mammalian (mouse, human, and ovine) leptins (Denbow et al, 2000 ; Dridi et al, 2000 ; Lohmus et al, 2003 ; Lõhmus et al, 2004 ; Manjunathan and Ragunathan, 2015 ). As the recombinant protein for the newly discovered chicken leptin (Seroussi et al, 2016 ) was not available at the time we undertook this study, we determined whether recombinant ovine leptin can modulate the autophagy pathway in vivo following ICV administration to broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sequence of chicken leptin gene was a matter of intense debate for almost 20 years (Taouis et al, 1998 ; Ashwell et al, 1999 ; Seroussi et al, 2016 ), the chicken leptin receptor sequence however was found to have at least 60% homology with the mammalian orthologs with highly conserved motifs in the transmembrane domain (Horev et al, 2000 ; Ohkubo et al, 2000 ). Moreover, previous in vitro and in vivo studies have shown that chicken leptin receptor is responsive to recombinant mammalian (mouse, human, and ovine) leptins (Denbow et al, 2000 ; Dridi et al, 2000 ; Lohmus et al, 2003 ; Lõhmus et al, 2004 ; Manjunathan and Ragunathan, 2015 ). As the recombinant protein for the newly discovered chicken leptin (Seroussi et al, 2016 ) was not available at the time we undertook this study, we determined whether recombinant ovine leptin can modulate the autophagy pathway in vivo following ICV administration to broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , LEP secreted from obese adipose tissue stromal cells enhanced growth of ER + breast cancer cells (36). LEP also stimulates angiogenesis ( 37 , 38 ). Therefore, in obese women, not only are there higher oestrogen levels but there are also higher levels of LEP which is tumourigenic both through its direct actions and possibly by its ability to stimulate the RAS, although it is only one of a number of pathways through which Ang II levels are increased in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…One such study by Huang et al [ 26 ] demonstrated that Phyllanthus urinaria efficiently inhibited embryonic angiogenesis by reducing the MMP-2 activity in the CAM model. Another interesting research conducted by Manjunathan et al [ 27 ] explained the positive angiogenic activity of human recombinant leptin (HRL) in chick CAM model. Their findings verify that the angiogenic response of HRL was due to increase in MMP-2 levels in CAM which caused breakdown of ECM in favour of migration and proliferation of ECs thus supporting the occurrence of sprouting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%